2020
DOI: 10.1136/bmjgast-2020-000430
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the rates of adherence to surveillance recommendations for incidental pancreatic cystic lesions in a large urban safety net hospital

Abstract: BackgroundPancreatic cystic lesions (PCLs) are a heterogenous group of lesions with varying degrees of malignant potential. PCLs are often incidentally detected on imaging. Management for patients without an immediate indication for resection or tissue sampling entails radiographic surveillance to assess for features concerning for malignant transformation. This study aims to determine the rates of adherence to surveillance recommendations for incidental PCLs, and identify factors associated with adherence or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Adherence rate in our study appears to be concordant with a similar single center retrospective study conducted in 123 subjects with PCNs that showed 71.5% completion of recommended follow-up. [ 10 ] In contrast, two other studies found a compliance rate less than 50%. More specifically, in a cohort of 100 patients with incidentally identified pancreatic cysts, 47% of patients followed the recommended surveillance, whereas in the second study only 42% adhered to follow-up guidelines.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Adherence rate in our study appears to be concordant with a similar single center retrospective study conducted in 123 subjects with PCNs that showed 71.5% completion of recommended follow-up. [ 10 ] In contrast, two other studies found a compliance rate less than 50%. More specifically, in a cohort of 100 patients with incidentally identified pancreatic cysts, 47% of patients followed the recommended surveillance, whereas in the second study only 42% adhered to follow-up guidelines.…”
Section: Discussionmentioning
confidence: 92%
“…Canakis et al . [ 10 ] concluded that cyst size smaller than 1.5 cm was associated with incompletion of follow-up, although statistical significance was not reached. Schenck et al [ 11 ] observed that the size and location of the lesion do not influence the compliance to follow-up, whereas MPD dilation and the absence of multiple cysts were predictors of higher adherence rates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These calculations did not factor in the cost of surgery or EUS. There is also the concern that patients can be lost to follow up with recent studies finding that 47% to 71.5% of patients received follow-up imaging for incidental cysts [ 106 , 107 ]. In a large urban safety net hospital, access to gastroenterology care was associated with surveillance completion [ 106 ].…”
Section: Approach To Pancreatic Cystmentioning
confidence: 99%